2018
DOI: 10.1021/acs.chemmater.7b04428
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Aqueous CO2 to 1-Propanol at MoS2 Electrodes

Abstract: Reduction of carbon dioxide in aqueous electrolytes at single-crystal MoS 2 or thin-film MoS 2 electrodes yields 1-propanol as the major CO 2 reduction product, along with hydrogen from water reduction as the predominant reduction process. Lower levels of formate, ethylene glycol, and t-butanol were also produced. At an applied potential of -0.59 V versus a reversible hydrogen electrode, the Faradaic efficiencies for reduction of CO 2 to 1-propanol were ~3.5% for MoS 2 single crystals and ~1% for thin films wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 25 publications
2
79
1
Order By: Relevance
“…It is considered that this is due to the MoS 2 layer stack, causing a "pile up" effect, further leading to slow charge transfer. [23,35] The results are consistent with the other analysis. Controlled potential electrolysis was performed to investigate the effect of applied potentials on FE and current density for HCOOH production at 5 % MS/SON electrode.…”
Section: Product Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…It is considered that this is due to the MoS 2 layer stack, causing a "pile up" effect, further leading to slow charge transfer. [23,35] The results are consistent with the other analysis. Controlled potential electrolysis was performed to investigate the effect of applied potentials on FE and current density for HCOOH production at 5 % MS/SON electrode.…”
Section: Product Analysissupporting
confidence: 91%
“…In order to seek good catalytic activity, researchers have tried to combine the two kinds of materials by various methods. Francis [23] et al synthesized MoS 2 thin-film catalysts on Si wafers with 1-Propanol Faradaic efficiency of 45 % and high stability of more than 12 h. Jung [24] et al immobilized hierarchical structure of mesoporous TiO 2 on 3D graphene with few-layered MoS 2 , and they found that the hierarchical structure contributed CO photoconversion, and the conversion rate (92.33 μmol CO/g h) was much higher than those of other structural composite combinations. Qiao [25] et al prepared MoS 2 /SnO 2 PÀ N Heterojunctions for trimethylamine gas sensor, the results showed that with low loading of MoS 2 , the PÀ N heterojunction exhibited superior sensing selectivity and long-term stability toward trimethylamine.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous section, we showed that multiple pathways startingf rom the adsorption of HCHO could open at À0.40 V. This value of h theory is consistent with the onset potential between À0.59 and À0.50 Vi ne xperiments associated with the formation of 1-propanol, the major CO 2 Rp roduct, but also ethylene glycol. [20] We note that the pH in the experiments was 6.8, which is slightly smaller than 7.0 in our calculations. This pH difference changed the h theory by approximately 0.01 V, barely affectingour conclusion.…”
Section: Comparison With Experimentscontrasting
confidence: 55%
“…[17][18][19] Recently,Francis et al investigated CO 2 Ro ns ingle-crystal MoS 2 in aqueous electrolyte, dis-covering1 -propanol (CH 3 CH 2 CH 2 OH)a sam ajor CO 2 Rp roduct at moderate overpotentials (%À0.59 Vv s. RHE), although the CO 2 Re fficiency was still outperformed by the hydrogen evolution reaction( HER). [20] This result is surprising because C 3 species are rarely produced as am ajor product of CO 2 Ro nk nown catalysts, particularly at such small overpotentials. The only exception that we are aware of are nickel phosphides, which were recentlyr eported to generate methylglyoxal (CH 3 COCHO) and ring-shaped 2,3-furandiol (C 4 H 4 O 3 )a sm ajor products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation